Detection and sequence analysis of enzyme genes of four thermo-tolerant bacillus pumilus strains from the Philippines - Malit, Jessie James L.; Hedreyda, Cynthia T. (2018)
The Philippines boasts of diversity in bacterial species that can be explored in producing industrially significant enzymes to help reduce the countryâ??s dependence on enzyme importation. This study was focused on four thermotolerant strains of Bacillus pumilus, a species reported to produce serine alkaline protease, lipase, pectate lyase, and laccase. Enzyme gene targeted polymerase chain reaction (PCR) and gene sequence analysis confirmed the presence of four enzyme genes in all strains studied. Preliminary enzyme assays revealed that all strains except 1271, tested positive for protease, pectate lyase, and lipase activities. Only strain 1271, however, exhibited positive laccase activity. These initial results could be the basis for pursuing studies on laccase using strain 1271 and studies on protease, pectate lyase and lipase enzymes from the other three strains. Partial amino acid sequence of the serine alkaline protease gene in strain 1271 revealed five amino acid variations from the other three strains and the variations resulted in protein conformational changes. The translated partial laccase gene sequence of strain 1271 exhibited ten amino acid variations from partial laccase enzymes of the other three strains but the amino acid variations did not result in enzyme conformation change. The amino acid sequences in the complete lipase genes showed five amino acid variations in isolate 1271 compared with enzymes from other three strains but no change in the predicted protein model was observed. Sixteen variations in the amino acid sequences of the pectate lyase enzyme observed among strains resulted in a unique pectate lyase protein conformation for each isolate. The role of enzyme conformation variation as well as other factors that could have led to the enzyme assay results in this study, could be further elucidated with optimized quantitative enzyme assays, gene expression studies and mutagenesis.